Solid electrolytic capacitor with stable electrical properties at high temperatures

By using a curable resin matrix material with a low thermal expansion coefficient to encapsulate the capacitor, the problem of deterioration of electrical performance caused by cracking at high temperatures is solved, and the stability and reliability of electrical performance at high temperatures is achieved.

JP2025020332APending Publication Date: 2025-02-12KYOCERA AVX COMPONENTS CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024195021
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-06-21
Filing Date
2024-11-07
Publication Date
2025-02-12

AI Technical Summary

Technical Problem

Existing solid-state electrolytic capacitors are prone to cracking of shell materials and rapid deterioration of electrical properties due to residual moisture evaporation under high temperature conditions, and cannot maintain stable electrical properties.

Method used

The capacitor is encapsulated with a curable resin matrix material with a low coefficient of thermal expansion to ensure that it is not prone to cracking at high temperatures and remains stable at high temperatures by controlling the equivalent series resistance and capacitance value of the capacitor.

Benefits of technology

At high temperature, the equivalent series resistance and capacitance value of the capacitor change is less than the predetermined range, maintaining good electrical performance and reducing the risk of cracking caused by thermal expansion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025020332000001_ABST
    Figure 2025020332000001_ABST
Patent Text Reader

Abstract

To improve a solid electrolytic capacitor such that the equivalence series resistance (ESR) does not increase after high temperature storage testing.SOLUTION: In an electrolytic capacitor 30, a resin material for use in a casing material 28 in which a capacitor element 33 is encapsulated is a curable resinous matrix with a coefficient of thermal expansion of about 42 ppm / °C or less at a temperature above the glass transition temperature thereof, and typically contains an epoxy resin. Such a capacitor exhibits an equivalence series resistance of about 200 mΩ or less under a prescribed initial condition, where the ratio of the equivalence series resistance after 125°C prescribed exposure testing is about 2 or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of U.S. Provisional Patent Application No. 62 / 687,961, having a filing date of June 21, 2018, which is incorporated by reference in its entirety. [Background technology]

[0002] Electrolytic capacitors (e.g., tantalum capacitors) are increasingly being used in circuit design due to their volumetric efficiency, reliability, and process compatibility. For example, one type of capacitor that has been developed is the solid electrolytic capacitor, which includes a tantalum anode, a dielectric layer, and a conductive polymer solid electrolyte. To help protect the capacitor from the external environment and give it good mechanical stability, the capacitor element is also typically fabricated such that a portion of the anode termination and cathode termination are maintained exposed for surface mounting. In general, solid electrolytic capacitors are encapsulated in a casing material (e.g., epoxy resin) as described above. Unfortunately, the high temperatures often used during capacitor manufacturing (e.g., reflow) can cause residual moisture to evaporate as water vapor, which is expelled from the case with considerable force, which can cause microcracks to form in the casing material. These microcracks can also cause delamination of the casing material from the capacitor element and rapid degradation of electrical properties, especially when the capacitor is exposed to high temperatures. Thus, a need exists for improved solid electrolytic capacitors that exhibit relatively stable electrical properties at high temperatures. Summary of the Invention

[0003] According to one embodiment of the present invention, a solid electrolytic capacitor is disclosed that includes a capacitor element including a sintered porous anode body, a dielectric disposed on the anode body, and a solid electrolyte disposed on the dielectric; an anode lead extending from a surface of the capacitor element; an anode termination electrically connected to the anode lead; a cathode termination electrically connected to the solid electrolyte; and a casing material encapsulating the capacitor element and the anode lead. The casing material is formed from a curable resinous matrix having a thermal expansion coefficient of about 42 ppm / °C or less at a temperature above the glass transition temperature of the resinous matrix. Furthermore, the capacitor exhibits an initial equivalent series resistance of about 200 milliohms or less determined at an operating frequency of 100 kHz and a temperature of 23°C, and the ratio of the equivalent series resistance of the capacitor after exposure to a temperature of 125°C for 560 hours to the initial equivalent series resistance of the capacitor is about 2.0 or less.

[0004] Other features and embodiments of the invention are set forth in more detail below. A full and enabling disclosure of the present invention, including the best mode thereof, directed to one of ordinary skill in the art, is set forth more particularly in the remainder of the specification, which makes reference to the appended drawings. [Brief description of the drawings]

[0005] [Figure 1] FIG. 1 is a schematic diagram of one embodiment of a solid electrolytic capacitor that may be formed in accordance with the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0006] Repeat use of reference characters in the present specification and drawings is intended to represent same or analogous features or components of the invention. This discussion is a description of exemplary embodiments only and is not intended to limit the broader aspects of the invention, which will be understood by those skilled in the art to be embodied in the exemplary configurations.

[0007] In general, the present invention includes a porous anode body, a dielectric disposed over the anode body, and a dielectric layer disposed over the dielectric. The present invention relates to a solid electrolytic capacitor including a capacitor element including a solid electrolyte disposed on an anode body. An anode lead extends from the anode body and is in electrical contact with the anode termination. The cathode termination is also in electrical contact with the solid electrolyte. A casing material further encapsulates the capacitor element and the anode lead, leaving at least a portion of the anode termination and cathode termination exposed for external contact. The casing material is formed from a curable resinous matrix having a relatively low coefficient of thermal expansion. For example, the resinous matrix typically has a coefficient of thermal expansion of about 42 ppm / °C or less, in some embodiments about 40 ppm / °C or less, and in some embodiments about 20 ppm / °C to about 38 ppm / °C at temperatures above the glass transition temperature of the resinous matrix. Furthermore, the resinous matrix also typically has a coefficient of thermal expansion of about 11 ppm / °C or less, in some embodiments about 10 ppm / °C or less, and in some embodiments about 1 to about 9 ppm / °C at temperatures below the glass transition temperature of the resinous matrix. The glass transition temperature of the resinous matrix may range, for example, from about 50° C. to about 180° C., in some embodiments from about 60° C. to about 160° C., and in some embodiments, from about 80° C. to about 150° C. The coefficient of thermal expansion and glass transition temperature may be determined using techniques known in the art, such as by thermomechanical analysis (TMA) according to ISO-11359-2:1999. Without intending to be limited by theory, it is believed that the use of a resinous matrix having such a low coefficient of thermal expansion may result in a casing material that is less likely to delaminate from the capacitor element when exposed to high temperatures often experienced during the manufacture (e.g., reflow) of capacitors.

[0008] By selectively controlling the particular properties of the casing material and the interfacial coating, the resulting capacitor can be made resistant to delamination during fabrication and can thus exhibit superior electrical properties. For example, the capacitors can exhibit relatively low equivalent series resistance (ESR), such as about 200 milliohms, in some embodiments less than about 150 milliohms, in some embodiments from about 0.1 to about 125 milliohms, and in some embodiments, from about 1 to about 100 milliohms, measured at an operating frequency of 100 kHz and a temperature of 23° C. The capacitors also exhibit a relatively low equivalent series resistance (ESR), such as about 30 nanofarads per square centimeter (nF / cm), measured at a frequency of 120 Hz and a temperature of 23° C. 2 ) or more, in some embodiments, about 100 nF / cm 2 In some embodiments, the range is about 200 to about 3,000 nF / cm 2 In some embodiments, the range is from about 400 to about 2,000 nF / cm 2 The dry capacitance can also be shown.

[0009] In particular, such electrical properties (e.g., ESR and / or capacitance) can be maintained in a stable state even at high temperatures. For example, the capacitor can exhibit ESR and / or capacitance values ​​within the above ranges even after exposure to temperatures of about 80° C. or higher, in some embodiments, about 100° C. to about 150° C., in some embodiments, about 105° C. to about 130° C. (e.g., 105° C. or 125° C.), for a considerable period of time, such as about 560 hours or more, in some embodiments, about 700 hours to about 2,000 hours, and in some embodiments, about 900 hours to about 1,500 hours (e.g., 240, 420, 560, 750, 1,000, or 1,250 hours). In one embodiment, for example, the ratio of the ESR and / or capacitance value of a capacitor after exposure to an elevated temperature (e.g., 125°C) for 560, 750, 1,000, and / or 1,250 hours to the initial ESR and / or capacitance value of the capacitor (e.g., at 23°C) is about 2.0 or less, in some embodiments about 1.5 or less, and in some embodiments from 1.0 to about 1.3. The capacitors can also exhibit ESR and / or capacitance values ​​within the above ranges after exposure to elevated relative humidity levels at either room temperature or elevated temperatures (e.g., 85°C or 125°C). Such elevated relative humidity levels can be, for example, about 40% or more, in some embodiments about 45% or more, in some embodiments about 50% or more, and in some embodiments about 70% or more (e.g., about 85% to 100%) for the substantial times described above. Relative humidity can be measured, for example, according to ASTM-E337-02, Method A (200 7) In one embodiment, for example, the ratio of the ESR and / or capacitance value of a capacitor after exposure to high humidity (e.g., 85%) for 240 hours to the initial ESR and / or capacitance value of the capacitor is about 2.0 or less, in some embodiments about 1.5 or less, and in some embodiments, from 1.0 to about 1.3.

[0010] Additionally, the capacitors may also exhibit a DCL of only about 50 microamps (μA) or less, in some embodiments about 40 μA or less, in some embodiments about 20 μA or less, and in some embodiments, about 0.1 to about 10 μA. Additionally, the capacitors may also exhibit a high percentage of their wet capacitance, allowing them to have only a small capacitance loss and / or change in the presence of atmospheric humidity. This performance characteristic is represented by the formula: Recovery rate = (dry capacitance / wet capacitance) x 100 This is quantified by the "capacitance recovery rate" given by:

[0011] The present capacitors may exhibit a capacitance recovery rate of about 50% or greater, in some embodiments about 60% or greater, in some embodiments about 70% or greater, and in some embodiments, about 80%-100%.

[0012] Various embodiments of the capacitor will now be described in more detail. I. Capacitor element: A. Anode body: The capacitor element includes an anode comprising a dielectric formed on a sintered porous body. The porous anode body can be formed from a powder including a valve metal (i.e., a metal that can be oxidized) or a valve metal-based compound, such as tantalum, niobium, aluminum, hafnium, titanium, alloys thereof, oxides thereof, nitrides thereof, and the like. The powder is typically a tantalum salt (e.g., potassium fluorotantalate (K 2 TaF 7 ), Sodium fluorotantalate (Na 2 TaF 7 ), Tantalum Pentachloride (TaCl 5 ) with a reducing agent. The reducing agent can be provided in the form of a liquid, gas (e.g., hydrogen), or a solid, such as a metal (e.g., sodium), a metal alloy, or a metal salt. For example, in one embodiment, a tantalum salt (e.g., TaCl 5) can be heated at a temperature of about 900° C. to about 2,000° C., in some embodiments about 1,000° C. to about 1,800° C., in some embodiments about 1,100° C. to about 1,600° C. to form a vapor, which can be reduced in the presence of a gaseous reducing agent (e.g., hydrogen). Further details of such reduction reactions are described in WO-2014 / 199480 by Maeshima et al. After reduction, the product can be cooled, crushed, and washed to form a powder.

[0013] The specific charge of the powder typically ranges from about 2,000 to about 600,000 microfarads·volts per gram (μF·V / g) depending on the desired application. For example, in some embodiments, high charge powders can be used having a specific charge of about 100,000 to about 550,000 μF·V / g, in some embodiments, about 120,000 to about 500,000 μF·V / g, and in some embodiments, about 150,000 to about 400,000 μF·V / g. In other embodiments, low charge powders can be used having a specific charge of about 2,000 to about 100,000 μF·V / g, in some embodiments, about 5,000 to about 80,000 μF·V / g, and in some embodiments, about 10,000 to about 70,000 μF·V / g. As is known in the art, the specific charge can be determined by multiplying the capacitance by the anodization voltage used and then dividing this product by the weight of the anodized electrode body.

[0014] The powder may be a free-flowing fine powder comprising primary particles. The primary particles of the powder are generally Typically, the particle size distribution is about 5% or less, as determined using, for example, a laser particle size distribution analyzer (e.g., LS-230) manufactured by BECKMAN COULTER Corporation, in some cases after subjecting the particles to ultrasonic vibration for 70 seconds. The primary particles typically have a three-dimensional particle shape (e.g., spherical or angular). Such particles typically have a relatively low "aspect ratio," i.e., the average diameter or width of the particle divided by the average thickness (D / T). For example, the aspect ratio of the particles may be about 4 or less, in some embodiments about 3 or less, and in some embodiments about 1 to about 2. In addition to the primary particles, the powder may contain other types of particles, such as secondary particles formed by aggregation (or agglomeration) of the primary particles. Such secondary particles may have a median diameter (D50) of about 1 to about 500 micrometers, in some embodiments about 10 to about 250 micrometers.

[0015] The particles can be aggregated by heating the particles and / or by using a binder, for example, at a temperature of about 0° C. to about 40° C., in some embodiments, about 5° C. to about 35° C., and in some embodiments, about 15° C. to about 30° C. Suitable binders may also include, for example, poly(vinyl butyral); poly(vinyl acetate); poly(vinyl alcohol); poly(vinylpyrrolidone); cellulose polymers such as carboxymethyl cellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, and methylhydroxyethyl cellulose; atactic polypropylene, polyethylene; polyethylene glycols (e.g., Carbowax from Dow Chemical Co.); polystyrene, poly(butadiene / styrene); polyamides, polyimides, and polyacrylamides, high molecular weight polyethers; copolymers of ethylene oxide and propylene oxide; fluoropolymers such as polytetrafluoroethylene, polyvinylidene fluoride, and fluoroolefin copolymers; acrylic polymers such as sodium polyacrylate, poly(lower alkyl acrylates), poly(lower alkyl methacrylates), and copolymers of lower alkyl acrylates and methacrylates; and fatty acids and waxes such as stearic acid and other soap fatty acids, vegetable waxes, microcrystalline waxes (refined paraffins), and the like.

[0016] The resulting powder can be compressed to form pellets using any conventional powder pressing equipment. For example, a press can be used that is a single station compression press that includes a die and one or more punches. Alternatively, an anvil type compression press can be used that uses only a die and a single lower punch. Single station compression presses are available in several basic types such as cam presses, toggle / knuckle presses, and eccentric / crank presses with various capabilities such as single action, double action, floating die, moving platen, opposed ram, screw, impact, hot pressing, coining, or sizing. The powder can be compressed around the anode lead, which can be in the form of a wire, sheet, or the like. The lead can extend longitudinally from the anode body and can be formed from any conductive material such as tantalum, niobium, aluminum, hafnium, titanium, and the like, as well as conductive oxides and / or nitrides thereof. Connection of the lead can also be accomplished using other known techniques, for example, by welding the lead to the anode body or embedding it within the anode body during formation (e.g., prior to compression and / or sintering).

[0017] The binder can be removed after pressing by heating the pellets under vacuum at a certain temperature (e.g., about 150°C to about 500°C) for several minutes. Alternatively, the binder can be removed by contacting the pellets with an aqueous solution such as that described in U.S. Patent 6,197,252 to Bishop et al. The pellets are then sintered to form a porous, integral member. The pellets are typically sintered at about 700°C to about 1800°C, and in some embodiments, at about 100°C to about 500°C. In some embodiments, the sintering is performed at a temperature of about 800°C to about 1700°C, and in some embodiments, about 900°C to about 1400°C, for about 5 minutes to about 100 minutes, and in some embodiments, about 8 minutes to about 15 minutes. This can be done in one or more steps. If desired, the sintering can be performed in an atmosphere that limits the migration of oxygen atoms to the anode. For example, the sintering can be performed in a reducing atmosphere, such as under vacuum, under an inert gas, or under hydrogen. The reducing atmosphere can be at a pressure of about 10 Torr to about 2000 Torr, and in some embodiments, about 100 Torr to about 1000 Torr, and in some embodiments, about 100 Torr to about 930 Torr. Mixtures of hydrogen and other gases, such as argon or nitrogen, can also be used.

[0018] B. Dielectric: The anode is also coated with a dielectric. The dielectric can be formed by anodizing a sintered anode such that a dielectric layer is formed on and / or within the anode. For example, a tantalum (Ta) anode can be anodized to form a tantalum pentoxide (Ta 2 O 5 ). Typically, anodization is performed by first applying a solution to the anode, such as by immersing the anode in the electrolyte. A solvent such as water (e.g., deionized water) is commonly used. To increase ionic conductivity, compounds that can dissociate in the solvent to form ions can be used. Examples of such compounds include acids, such as those described below with respect to the electrolyte. For example, an acid (e.g., phosphoric acid) can constitute from about 0.01% to about 5% by weight, in some embodiments from about 0.05% to about 0.8% by weight, and in some embodiments from about 0.1% to about 0.5% by weight of the anodization solution. Blends of acids can also be used if desired.

[0019] A current is passed through the anodizing solution to form the dielectric layer. The thickness of the dielectric layer is controlled by the value of the anodizing voltage. For example, the power supply can first be set in constant current mode until the required voltage is reached. The power supply can then be switched to constant potential mode to ensure that the desired dielectric thickness is formed over the entire surface of the anode. Of course, other known methods such as pulse or step potentiostatic methods can also be used. The voltage at which the anodization is performed is typically in the range of about 4 to about 250 V, in some embodiments about 5 to about 200 V, and in some embodiments about 10 to about 150 V. During oxidation, the anodizing solution can be maintained at an elevated temperature, for example, at about 30° C. or higher, in some embodiments about 40° C. to about 200° C., and in some embodiments about 50° C. to about 100° C. Anodization can also be performed at or below ambient temperature. The resulting dielectric layer can be formed on the surface of the anode and within its pores.

[0020] Although not required, in some embodiments, the dielectric layer can have a differentiated thickness throughout the anode in that it has a first portion disposed on the outer surface of the anode and a second portion disposed on the inner surface of the anode. In such embodiments, the first portion is selectively formed such that its thickness is greater than the thickness of the second portion. However, it should be understood that the thickness of the dielectric layer need not be uniform within a particular region. Some portions of the dielectric layer adjacent to the outer surface, for example, may actually be thinner than some portions of the layer at the inner surface, and vice versa. Nevertheless, the dielectric layer can be formed such that at least a portion of the layer at the outer surface has a greater thickness than at least a portion at the inner surface. While the actual difference in these thicknesses can vary depending on the particular application, the ratio of the thickness of the first portion to the thickness of the second portion is typically about 1.2 to about 40, in some embodiments about 1.5 to about 25, and in some embodiments about 2 to about 20.

[0021] A multi-step process is commonly used to form dielectric layers of differentiated thickness. In each step of the process, a sintered anode is anodized to form a dielectric layer (e.g., tantalum pentoxide). During the first step of anodization, a relatively small formation voltage is usually applied, For example, a formation voltage in the range of about 1 to about 90 volts, in some embodiments about 2 to about 50 volts, and in some embodiments about 5 to about 20 volts, is used to ensure that the desired dielectric thickness is achieved for the interior region. The sintered body can then be anodized in a second stage of the process to increase the dielectric thickness to the desired level. This is generally accomplished by anodizing in an electrolyte at a formation voltage higher than that used in the first stage, for example, in the range of about 50 to about 350 volts, in some embodiments about 60 to about 300 volts, and in some embodiments about 70 to about 200 volts. During the first and / or second stages, the electrolyte can be maintained at a temperature in the range of about 15° C. to about 95° C., in some embodiments about 20° C. to about 90° C., and in some embodiments about 25° C. to about 85° C.

[0022] The electrolyte used during the first and second stages of the anodization process may be the same or different. However, it is usually desirable to use different solutions to help better facilitate obtaining a greater thickness at the outer portion of the dielectric layer. For example, it may be desirable for the electrolyte used during the second stage to have a lower ionic conductivity than the electrolyte used during the first stage, so that a significant amount of oxide film is not formed on the inner surface of the anode. In this regard, the electrolyte used during the first stage may include an acidic compound, such as nitric acid, sulfuric acid, phosphoric acid, polyphosphoric acid, boric acid, boronic acid, and the like. Such electrolytes may have a conductivity of about 0.1 to about 100 mS / cm, in some embodiments about 0.2 to about 20 mS / cm, and in some embodiments about 1 to about 10 mS / cm, measured at a temperature of 25° C. The electrolyte used during the second stage usually includes a salt of a weak acid so that the hydronium ion concentration increases in the pores as a result of the passage of charge therethrough. Ion transport or diffusion occurs such that anions of the weak acid migrate into the pores as needed to balance the charge. As a result, the concentration of the main conductive species (hydronium ions) decreases as an equilibrium is formed between hydronium ions, acid anions, and undissociated acid, forming poorly conductive species. The decrease in the concentration of the conductive species results in a relatively high voltage drop in the electrolyte, which prevents further anodization in the interior, while a thicker oxide layer accumulates on the exterior for high formation voltages in the successive high conductivity regions. Suitable weak acid salts include, for example, ammonium or alkali metal salts (e.g., sodium, potassium, etc.) of boric acid, boronic acid, acetic acid, oxalic acid, lactic acid, adipic acid, and the like. Particularly suitable salts include sodium tetraborate and ammonium pentaborate. Such electrolytes typically have a conductivity of about 0.1 to about 20 mS / cm, in some embodiments about 0.5 to about 10 mS / cm, and in some embodiments about 1 to about 5 mS / cm, measured at a temperature of 25°C.

[0023] If desired, each step of anodization can be repeated one or more times to achieve the desired dielectric thickness. Additionally, the anode can be rinsed or washed with other solvents (e.g., water) after the first and / or second steps to remove the electrolyte.

[0024] C. Solid electrolyte: A solid electrolyte is disposed over the dielectric and typically functions as the cathode for the capacitor. Solid electrolytes can include materials known in the art such as conductive polymers (e.g., polypyrroles, polythiophenes, polyanilines, etc.), manganese dioxide, and the like. In one embodiment, for example, the solid electrolyte includes one or more layers that include extrinsically conductive and / or intrinsically conductive polymer particles. One benefit of using such particles is that they provide a cost-effective alternative to conventional in-situ polymer deposition. Ion species (e.g., Fe) that are generated during the bonding process and can cause dielectric breakdown under high electric fields due to ion migration. 2+ or Fe 3+ Thus, by applying the conductive polymer as pre-polymerized particles rather than by in-situ polymerization, the resulting capacitor has a relatively high "breakdown voltage" If desired, the solid electrolyte may be formed from one or more layers. When multiple layers are used, one or more of the layers may include a conductive layer formed by in-situ polymerization. However, when it is desired to achieve very high breakdown voltages, it is preferred that the solid electrolyte be formed primarily from the conductive particles described above and not include conductive polymers, which are generally formed by in situ polymerization. Regardless of the number of layers used, the resulting solid electrolyte typically has a total thickness of from about 1 micrometer (μm) to about 200 μm, in some embodiments from about 2 μm to about 50 μm, and in some embodiments, from about 5 μm to about 30 μm.

[0025] Thiophene polymers are particularly suitable for use in solid electrolytes. For example, in some embodiments, the thiophene polymers have the following formula (I):

[0026] [ka]

[0027] (In the formula, R 7 is linear or branched, C 1 ~C 18 Alkyl groups (e.g., methyl, ethyl, n- or isopropyl, n-, iso-, sec-, or tert-butyl, n-pentyl, 1-methylbutyl, 2-methylbutyl, 3-methylbutyl, 1-ethylpropyl, 1,1-dimethylpropyl, 1,2-dimethylpropyl, 2,2-dimethylpropyl, n-hexyl, n-heptyl, n-octyl, 2-ethylhexyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, n-tridecyl, n-tetradecyl, n-hexadecyl, n-octadecyl, etc.); C 5 ~C 12 Cycloalkyl groups (e.g., cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, cyclodecyl, etc.); C 6 ~C 14 Aryl groups (e.g., phenyl, naphthyl, etc.); C 7 ~C 18 aralkyl groups (e.g., benzyl, o-, m-, p-tolyl, 2,3-, 2,4-, 2,5-, 2,6-, 3,4-, 3,5-xylyl, mesityl, etc.); q is an integer of 0 to 8, in some embodiments 0 to 2, and in one embodiment 0. An "extrinsic" conductive thiophene polymer having a repeat unit of the formula: can be used in the solid electrolyte. In one particular embodiment, "q" is 0 and the polymer is poly(3,4-ethylenedioxythiophene). One commercially suitable example of a suitable monomer for forming such a polymer is available from Heraeus under the name Clevios® M. The most commonly available compound is 3,4-ethylenedioxythiophene.

[0028] The polymers of formula (I) are generally considered to be "extrinsically" conductive in that they usually require the presence of another counterion that is not covalently bonded to the polymer. The counterion may be a monomeric or polymeric anion that neutralizes the charge of the conductive polymer. The polymeric anion may be, for example, an anion of a polymeric carboxylic acid (e.g., polyacrylic acid, polymethacrylic acid, polymaleic acid, etc.); a polymeric sulfonic acid (e.g., polystyrene sulfonic acid (PSS), polyvinyl sulfonic acid, etc.); and the like. The acid may also be a copolymer, such as a copolymer of vinyl carboxylic acid and vinyl sulfonic acid with other polymerizable monomers, such as acrylic acid esters and styrene. Additionally, suitable monomeric anions include, for example, C 1 ~C 20 Alkanesulfonic acids (e.g. dodecanesulfonic acid); aliphatic perfluoro sulfonic acids (e.g., trifluoromethanesulfonic acid, perfluorobutanesulfonic acid, or perfluorooctanesulfonic acid); aliphatic C 1 ~C 20 Carboxylic acids (e.g., 2-ethylhexyl carboxylic acid); aliphatic perfluorocarboxylic acids (e.g., trifluoroacetic acid or perfluorooctanoic acid); optionally C 1 ~C 20Examples of the counter anion include aromatic sulfonic acids substituted with alkyl groups (e.g., benzenesulfonic acid, o-toluenesulfonic acid, p-toluenesulfonic acid, or dodecylbenzenesulfonic acid); cycloalkanesulfonic acids (e.g., camphorsulfonic acid, or tetrafluoroborate, hexafluorophosphate, perchlorate, hexafluoroantimonate, hexafluoroarsenate, or hexachloroantimonate); and the like. Particularly suitable counter anions are polymeric anions such as polymeric carboxylic or sulfonic acids (e.g., polystyrene sulfonic acid (PSS)). The molecular weight of such polymeric anions is typically in the range of about 1,000 to about 2,000,000, and in some embodiments, about 2,000 to about 500,000.

[0029] Also, inherently conductive polymers can be used that have positive charges disposed on the backbone that are at least partially compensated by anions covalently attached to the polymer. For example, one example of a suitable inherently conductive thiophene polymer has the following formula (II):

[0030] [ka]

[0031] (In the formula, R is (CH 2 ) a -O-(CH 2 ) b -L, where L is a bond or HC([CH 2 ] c H) is; a is 0 to 10, in some embodiments 0 to 6, and in some embodiments 1 to 4 (e.g., 1); b is 1 to 18, in some embodiments 1 to 10, and in some embodiments 2 to 6 (e.g., 2, 3, 4, or 5); c is 0 to 10, in some embodiments 0 to 6, and in some embodiments 1 to 4 (e.g., 1); Z is SO3 - , C(O)O - , B.F. 4 - , C.F. 3 SO 3 - , SbF 6 - , N(SO 2 CF 3 ) 2 - , C 4 H 3 O 4 - , ClO 4 - etc., anions such as; X is a cation such as hydrogen, an alkali metal (e.g., lithium, sodium, rubidium, cesium, or potassium), ammonium, etc. It may have the repeat unit:

[0032] In one particular embodiment, Z in formula (II) is a sulfonate ion and the intrinsically conductive polymer has the following formula (III):

[0033] [ka]

[0034] (wherein R and X are as defined above). In formula (II) or (III), a is preferably 1, and b is preferably 3 or 4. Furthermore, X is preferably sodium or potassium.

[0035] If desired, the polymer may be a copolymer containing other types of repeat units. In such embodiments, the repeat units of formula (II) typically constitute at least about 50 mol %, in some embodiments from about 75 mol % to about 99 mol %, and in some embodiments from about 85 mol % to about 95 mol % of the total amount of repeat units in the copolymer. Of course, the polymer may be a homopolymer in that it contains 100 mol % of the repeat units of formula (II). Specific examples of such homopolymers include poly(4-(2,3-dihydrothieno-[3,4-b][1,4]dioxin-2-ylmethoxy)-1-butanesulfonic acid, salt) and poly(4-(2,3-dihydrothieno-[3,4-b][1,4]dioxin-2-ylmethoxy)-1-propanesulfonic acid, salt).

[0036] Regardless of the particular nature of the polymer, the resulting conductive polymer particles typically have an average size (e.g., diameter) of about 1 to about 80 nanometers, in some embodiments about 2 to about 70 nanometers, and in some embodiments about 3 to about 60 nanometers. The diameter of the particles can be determined using known techniques such as ultracentrifugation, laser diffraction, and the like. Additionally, the shape of the particles can vary. For example, in one particular embodiment, the particles are spherical in shape. However, it should be understood that other shapes, such as plates, rods, disks, bars, tubes, irregular shapes, and the like, are also contemplated by the present invention.

[0037] Although not required, the conductive polymer particles can be applied in the form of a dispersion. The concentration of the conductive polymer in the dispersion can vary depending on the desired viscosity of the dispersion and the particular method of applying the dispersion to the capacitor element. Typically, however, the polymer comprises from about 0.1 to about 10 weight percent of the dispersion, in some embodiments from about 0.4 to about 5 weight percent, and in some embodiments from about 0.5 to about 4 weight percent. The dispersion can also include one or more components to improve the overall properties of the resulting solid electrolyte. For example, the dispersion can include a binder to further enhance the adhesion of the polymer layer and also to increase the stability of the particles within the dispersion. The binder may be of organic nature such as polyvinyl alcohol, polyvinylpyrrolidone, polyvinyl chloride, polyvinyl acetate, polyvinyl butyrate, polyacrylic esters, polyacrylic amides, polymethacrylic esters, polymethacrylic amides, polyacrylonitrile, styrene / acrylic esters, vinyl acetate / acrylic esters and ethylene / vinyl acetate copolymers, polybutadiene, polyisoprene, polystyrene, polyethers, polyesters, polycarbonates, polyurethanes, polyamides, polyimides, polysulfones, melamine formaldehyde resins, epoxide resins, silicone resins or cellulose. Crosslinking agents may also be used to increase the adhesive ability of the binder. Such crosslinking agents may include, for example, melamine compounds, masked isocyanates or crosslinkable polymers such as polyurethanes, polyacrylates or polyolefins, which may include subsequent crosslinking. Dispersing agents may also be used to facilitate the ability to apply the layer to the anode. Suitable dispersing agents include aliphatic alcohols (e.g., methanol, ethanol, i- Examples of suitable dispersants include solvents such as propanol, butanol, aliphatic ketones (e.g., acetone and methyl ethyl ketone), aliphatic carboxylic acid esters (e.g., ethyl acetate and butyl acetate), aromatic hydrocarbons (e.g., toluene and xylene), aliphatic hydrocarbons (e.g., hexane, heptane, and cyclohexane), chlorinated hydrocarbons (e.g., dichloromethane and dichloroethane), aliphatic nitriles (e.g., acetonitrile), aliphatic sulfoxides and sulfones (e.g., dimethyl sulfoxide and sulfolane), aliphatic carboxylic acid amides (e.g., methylacetamide, dimethylacetamide, and dimethylformamide), aliphatic and araliphatic ethers (e.g., diethyl ether and anisole), water, and mixtures of any of the above solvents. A particularly suitable dispersant is water.

[0038] In addition to those mentioned above, further components can be used in the dispersion. For example, conventional fillers having dimensions of about 10 nanometers to about 100 micrometers, in some embodiments about 50 nanometers to about 50 micrometers, in some embodiments about 100 nanometers to about 30 micrometers can be used. Examples of such fillers include calcium carbonate, silicates, silica, calcium or barium sulfate, aluminum hydroxide, glass fibers or glass spheres, wood flour, cellulose powder, carbon black, conductive polymers, and the like. The fillers can be introduced into the dispersion in powder form, but can also be present in other forms, such as fibers.

[0039] Surface active substances such as ionic or non-ionic surfactants can also be used in the dispersion. In addition, adhesives such as organofunctional silanes or their hydrolysates, for example, 3-glycidoxypropyltrialkoxysilane, 3-aminopropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane or octyltriethoxysilane can be used. The dispersion can also contain ether group-containing compounds (e.g., tetrahydrofuran), lactone group-containing compounds (e.g., γ-butyrolactone or γ-valerolactone), amide or lactam group-containing compounds (e.g., caprolactam, N-methylcaprolactam, N,N-dimethylacetamide, N-methylacetamide, N,N-dimethylformamide (DMF), N-methylformamide, N-methylformanilide, N-methylpyrrolidone (NMP), N-octylpyrrolidone, or pyrrolidone), sulfones and Additives that increase conductivity may also be included, such as sulfoxides (e.g., sulfolane (tetramethylene sulfone) or dimethyl sulfoxide (DMSO)), sugars or sugar derivatives (e.g., saccharose, glucose, fructose, or lactose), sugar alcohols (e.g., sorbitol or mannitol), furan derivatives (e.g., 2-furan carboxylic acid or 3-furan carboxylic acid), alcohols (e.g., ethylene glycol, glycerol, di- or triethylene glycol).

[0040] The dispersion can be applied using a variety of known techniques, such as by spin coating, impregnation, pouring, drop application, injection, spraying, doctor blade application, brush application, printing (e.g., inkjet, screen, or pad printing), or immersion. The viscosity of the dispersion is typically from about 0.1 to about 100,000 mPas (100 s -1 In some embodiments, the shear velocity is about 1 to about 10,000 mPas, in some embodiments, about 10 to about 1,500 mPas, and in some embodiments, about 100 to about 1000 mPas.

[0041] i.Inner layer: The solid electrolyte is generally formed from one or more "inner" conductive polymer layers. The term "inner" in this context refers to one or more layers disposed on the dielectric, either directly or via another layer (e.g., a precoat layer). One or more inner layers can be used. For example, the solid electrolyte typically comprises 2-30, and in some embodiments 4-20, and in some embodiments 10-20, inner layers. In some embodiments, the inner layer or layers include about 5-15 inner layers (e.g., 10 layers). One or more of the inner layers can include, for example, intrinsically and / or extrinsically conductive polymer particles, as described above. For example, such particles can comprise about 50% or more by weight, in some embodiments about 70% or more by weight, and in some embodiments about 90% or more by weight (e.g., about 100% by weight) of the one or more inner layers. In another embodiment, one or more of the inner layers can include an in-situ polymerized conductive polymer. In such an embodiment, the in situ polymerized polymer may be one or more inner It may constitute about 50% or more by weight of the layer, in some embodiments about 70% or more by weight, and in some embodiments, about 90% or more by weight (eg, about 100% by weight).

[0042] ii. Outer layer: The solid electrolyte may also include one or more optional "outer" conductive polymer layers disposed on the inner layer or layers and formed from a different material. For example, the outer layer or layers may include extrinsic conductive polymer particles. In one particular embodiment, the outer layer or layers are formed primarily from such extrinsic conductive polymer particles in that the extrinsic conductive polymer particles constitute at least about 50% by weight, in some embodiments at least about 70% by weight, and in some embodiments at least about 90% by weight (e.g., 100% by weight) of the respective outer layer. One or more outer layers may be used. For example, the solid electrolyte may include 2-30, in some embodiments 4-20, and in some embodiments about 5-15 outer layers, each of which may optionally be formed from a dispersion of extrinsic conductive polymer particles.

[0043] D. Outer polymer coating: An external polymer coating can also be disposed on the solid electrolyte. The external polymer coating can include one or more layers formed from prepolymerized conductive polymer particles (e.g., a dispersion of exogenous conductive polymer particles) as described above. The external coating can further penetrate into the edge regions of the capacitor body to increase adhesion to the dielectric and provide a more mechanically robust part, which can reduce equivalent series resistance and leakage current. Generally, the particles used in the external coating will typically have a larger size than those used in the solid electrolyte, since they are intended to improve edge coverage rather than impregnate the interior of the anode body. For example, the ratio of the average size of the particles used in the external polymer coating to the average size of the particles used in any dispersion of the solid electrolyte is typically about 1.5 to about 30, in some embodiments about 2 to about 20, and in some embodiments about 5 to about 15. For example, the particles used in the dispersion of the external coating can have an average size of about 80 to about 500 nanometers, in some embodiments about 90 to about 250 nanometers, and in some embodiments about 100 to about 200 nanometers.

[0044] If desired, a crosslinking agent can be used in the outer polymer coating to increase adhesion to the solid electrolyte. Typically, the crosslinking agent is applied before applying the dispersion used in the outer coating. Suitable crosslinking agents are described, for example, in U.S. Patent Publication 2007 / 0064376 to Merker et al., and include, for example, amines (e.g., diamines, triamines, oligomeric amines, polyamines, etc.); salts or compounds of polyvalent metal cations, such as Mg, Al, Ca, Fe, Cr, Mn, Ba, Ti, Co, Ni, Cu, Ru, Ce, or Zn, phosphonium compounds, sulfonium compounds, and the like. Particularly preferred examples include 1,4-diaminocyclohexane, 1,4-bis(aminomethyl)cyclohexane, ethylenediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,12-dodecanediamine, N,N-dimethylethylenediamine, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetramethyl-1,4-butanediamine, and the like, as well as these Mixtures are also included.

[0045] The crosslinker is typically applied from a solution or dispersion whose pH is 1-10, in some embodiments 2-7, and in some embodiments 3-6, determined at 25° C. An acidic compound may be used to help achieve the desired pH level. Examples of solvents or dispersants for the crosslinker include water, or organic solvents, such as alcohols, ketones, carboxylic acid esters, and the like. The crosslinker may be applied to the capacitor body by any known process, such as spin coating, impregnation, casting, drop application, spray application, deposition, sputtering, sublimation, knife coating, painting, or printing, such as inkjet, screen, or pad printing. Once applied, the crosslinker may be dried before applying the polymer dispersion. This process may then be repeated until the desired thickness is achieved. For example, the total thickness of the entire outer polymer coating, including the layers of crosslinker and dispersion, may range from about 1 to about 50 μm, in some embodiments from about 2 to about 40 μm, and in some embodiments from about 5 to about 20 μm.

[0046] E. Cathode Coating: If desired, the capacitor element may also employ a cathode coating disposed over the solid electrolyte and other optional layers (e.g., an outer polymer coating). The cathode coating may include a metal particle layer including a multiplicity of conductive metal particles dispersed within a polymer matrix. The particles typically comprise from about 50% to about 99% by weight of the layer, in some embodiments from about 60% to about 98% by weight, and in some embodiments from about 70% to about 95% by weight, while the polymer matrix typically comprises from about 1% to about 50% by weight, in some embodiments from about 2% to about 40% by weight, and in some embodiments from about 5% to about 30% by weight of the layer.

[0047] The conductive metal particles can be formed from a variety of different metals, such as copper, nickel, silver, nickel, zinc, tin, lead, copper, aluminum, molybdenum, titanium, iron, zirconium, magnesium, and the like, as well as alloys thereof. Silver is a particularly suitable conductive metal for use in such layers. The metal particles often have relatively small dimensions, such as an average diameter of about 0.01 to about 50 micrometers, in some embodiments about 0.1 to about 40 micrometers, and in some embodiments about 1 to about 30 micrometers. It should be understood that, although typically only one layer of metal particles is used, multiple layers can be used if desired. The total thickness of such one or more layers is in the range of about 1 μm to about 500 μm, in some embodiments about 5 μm to about 200 μm, and in some embodiments about 10 μm to about 100 μm.

[0048] The polymer matrix typically comprises a polymer which may be thermoplastic or thermosetting in nature. However, typically the polymer is selected to contain a relatively small amount of polar groups which can act as a barrier to electromigration of silver ions and also minimize the degree of water adsorption in the cathode coating. In this regard, the inventors have found that vinyl acetal polymers such as polyvinyl butyral, polyvinyl formal, and the like are particularly suitable for this purpose. For example, polyvinyl butyral can be formed by reacting polyvinyl alcohol with an aldehyde (e.g., butyraldehyde). Because this reaction is usually not complete, polyvinyl butyral generally has a residual hydroxyl content. However, by minimizing this content, the polymer can have a lower degree of strongly polar groups which would otherwise cause a high degree of moisture adsorption and migration of silver ions. For example, the residual hydroxyl content in polyvinyl acetal can be about 35 mol % or less, in some embodiments about 30 mol % or less, and in some embodiments, about 10 mol % to about 25 mol %. One commercially available example of such a polymer is available from Sekisui Chemical Co. It is available from , Ltd. under the name "BH-S" (Polyvinyl Butyral).

[0049] To form the cathode coating, a conductive paste is typically applied to the capacitor over the solid electrolyte. One or more organic solvents are typically used in the paste. In general, a variety of different organic solvents can be used, such as glycols (e.g., propylene glycol, butylene glycol, triethylene glycol, hexylene glycol, polyethylene glycol, ethoxydiglycol, and dipropylene glycol); glycol ethers (e.g., methyl glycol ether, ethyl glycol ether, and isopropyl glycol ether); ethers (e.g., diethyl ether and tetrahydrofuran); alcohols (e.g., benzyl alcohol, methanol, ethanol, n-propanol, iso-propanol, and butanol); triglycerides; ketones (e.g., acetone, methyl ethyl ketone, and methyl isobutyl ketone); esters (e.g., ethyl acetate, butyl acetate, diethylene glycol ether acetate, and methoxypropyl acetate); amides (e.g., dimethylformamide, dimethylacetamide, dimethylcapryl / capric fatty acid amide, and N-alkylpyrrolidones); nitriles (e.g., acetonitrile, propiononitrile, butyronitrile, and benzonitrile); sulfoxides or sulfones (e.g., dimethylsulfoxide (DMSO) and sulfolane); and the like, as well as mixtures thereof. The organic solvent or solvents typically comprise about 10% to about 70% by weight of the paste, in some embodiments about 20% to about 65% by weight, and in some embodiments about 30% to about 60% by weight. The metal particles typically comprise about 10% to about 60% by weight of the paste, in some embodiments about 20% to about 45% by weight, and in some embodiments about 25% to about 40% by weight, and the resinous matrix typically comprises about 0.1% to about 20% by weight of the paste, in some embodiments about 0.2% to about 10% by weight, and in some embodiments about 0.5% to about 8% by weight.

[0050] The paste may have a relatively low viscosity, which allows it to be easily handled and applied to the capacitor element. Viscosity may be measured, for example, using a Brookfield DV-1 viscometer (cone The viscosity may range from about 50 to about 3,000 centipoise, in some embodiments from 100 to about 2,000 centipoise, and in some embodiments from about 200 to about 1,000 centipoise, as measured using a gypsum plate or the like operating at a speed of 10 rpm and a temperature of 25° C. If desired, thickeners or other viscosity modifiers can be used in the paste to increase or decrease the viscosity. Additionally, the paste may be applied at a relatively thin thickness and still achieve the desired properties. For example, the paste may be applied at a thickness of about 0.01 to about 50 micrometers, in some embodiments from about 0.5 to about 30 micrometers, and in some embodiments from about 1 to about 25 micrometers. Once applied, the metal paste may be optionally dried to remove some components such as organic solvents. For example, drying may be performed at a temperature of about 20° C. to about 150° C., in some embodiments from about 50° C. to about 140° C., and in some embodiments from about 80° C. to about 130° C.

[0051] F. Other Ingredients: If desired, other layers known in the art may also be included in the capacitor. For example, in some embodiments, a carbon layer (e.g., graphite) may be disposed between the solid electrolyte and the silver layer to help further limit contact between the silver layer and the solid electrolyte. Additionally, a precoat layer disposed over the dielectric and comprising an organometallic compound, as described in more detail below, may also be used.

[0052] II. Termination: Once the desired layers have been formed, the capacitor can be terminated as described above. More specifically, the capacitor includes an anode termination to which the anode lead of the capacitor element is electrically connected, and a cathode termination to which the solid electrolyte of the capacitor is electrically connected. Any conductive material can be used to form the terminations, such as conductive metals (e.g., copper, nickel, silver, nickel, zinc, tin, palladium, lead, copper, aluminum, molybdenum, titanium, iron, zirconium, magnesium, and alloys thereof). Particularly suitable conductive metals include, for example, copper, copper alloys (e.g., copper-zirconium, copper-magnesium, copper-zinc, or copper-iron), nickel, and nickel alloys (e.g., nickel-iron). The thickness of the terminations is generally selected to minimize the thickness of the capacitor. For example, the thickness of the terminations may range from about 0.05 to about 1 millimeter, in some embodiments, from about 0.05 to about 0.5 millimeters, and from about 0.07 to about 0.2 millimeters. One exemplary conductive material is a copper-iron alloy metal plate available from Wieland (Germany). If desired, the surfaces of the terminations can be electroplated with nickel, silver, gold, tin, etc., as is known in the art, to ensure that the final component can be mounted to a circuit board. In one particular embodiment, both surfaces of the terminations are plated with nickel and silver flash, respectively, while the mounting surface is also plated with a tin solder layer.

[0053] The terminations may be connected to the capacitor element using any technique known in the art. For example, in one embodiment, a lead frame may be provided that defines a cathode termination and an anode termination. To attach the capacitor element to the lead frame, a conductive adhesive may first be applied to the surface of the cathode termination. The conductive adhesive may include, for example, conductive metal particles contained in a resin composition. The metal particles may be silver, copper, gold, platinum, nickel, zinc, bismuth, or the like. The resin composition may include a thermosetting resin (e.g., an epoxy resin), a hardener (e.g., an acid anhydride), and a coupling agent (e.g., a silane coupling agent). Suitable conductive adhesives are described in U.S. Patent Application Publication No. 2004 / 0133935 to Osako et al. No. 2006 / 0038304. The conductive adhesive can be applied to the cathode termination using any of a variety of techniques. For example, printing techniques can be used for their practical and cost-saving benefits. The anode lead can also be electrically connected to the anode termination using any technique known in the art, such as mechanical welding, laser welding, conductive adhesives, etc. Once the anode lead is electrically connected to the anode termination, the conductive adhesive can then be cured to ensure proper adhesion of the electrolytic capacitor to the cathode termination.

[0054] For example, referring to FIG. 1, electrolytic capacitor 30 is shown as including an anode termination 62 and a cathode termination 72 in electrical contact with capacitor element 33 having top surface 37, bottom surface 39, front surface 36, back surface 38, first side 35, and an opposing side (not shown). Cathode termination 72 may be provided in electrical contact with any surface of capacitor element 33, for example, by a conductive adhesive. For example, in the embodiment shown, cathode termination 72 includes a first part 73 generally parallel to and adjacent top surface 37, and a second part 75 generally parallel to and adjacent bottom surface 39. First part 73 is also in electrical contact with top surface 37. Cathode termination 72 may also include a third part extending generally in a direction perpendicular to first part 73 and second part 75. If desired, third part 77 may also be provided in electrical contact with back surface 38 of capacitor element 33. Anode termination 62 also includes a first part 63 that is generally parallel to bottom surface 39 of capacitor element 33, and a second part 67 that is generally parallel to anode lead 16. Anode termination 62 may further include a third part 64 that is generally perpendicular to first part 63, and a fourth part 69 that is generally perpendicular to second part 67 and disposed adjacent anode lead 16. In the embodiment shown, second part 67 and fourth part 69 define region 51 for connection to anode lead 16. Although not shown in FIG. 1, region 51 may further improve surface contact and mechanical stability of lead 16. It may have a "U-shape" to increase the

[0055] The terminations may be connected to the capacitor element using any technique known in the art. For example, in one embodiment, a lead frame may be provided that defines a cathode termination 72 and an anode termination 62. To attach the capacitor element 33 to the lead frame, a conductive adhesive 49 may first be applied to a surface of the cathode termination 72. In one embodiment, the anode termination 62 and the cathode termination 72 are folded into the position shown in FIG. 1. The capacitor element 33 is then placed on the cathode termination 72 such that its underside 39 contacts the adhesive 49 and the anode lead 16 contacts the region 51. The anode lead 16 is then electrically connected to the region 51 using any technique known in the art, such as mechanical welding, laser welding, conductive adhesives, and the like. For example, the anode lead 16 may be welded to the anode termination 62 using a laser. A laser generally includes a resonator that includes a laser medium capable of emitting photons by stimulated emission, and an energy source that excites the elements of the laser medium. One type of suitable laser is one in which the laser medium consists of neodymium (Nd) doped aluminum and yttrium garnet (YAG). The excited particles are neodymium ions Nd 3+ The energy source can provide continuous energy to the laser medium to emit a continuous laser beam, or can provide an energy discharge to emit a pulsed laser beam. Once the anode lead 16 is electrically connected to the anode termination 62, the conductive adhesive can then be cured. For example, a heat press can be used to apply heat and pressure to ensure that the electrolytic capacitor element 33 is properly bonded to the cathode termination 72 by the adhesive 49.

[0056] To further help minimize the possibility of delamination, an interfacial coating may also be used that covers at least a portion of the anode and / or cathode terminations and contacts the casing material. Unlike the metallic components typically used in the anode and cathode terminations, the interfacial coating may be formed from a resinous material that has a substantially similar coefficient of thermal expansion as the curable resinous matrix used in the casing material. Again, this may further reduce the possibility that expansion of the casing material during manufacture will result in delamination from the anode lead and / or capacitor element.

[0057] One or more coatings may be used. For example, in one embodiment, an interfacial coating may be used that covers at least a portion of the anode termination. In such an embodiment, the coating may also contact at least a portion of a surface of the capacitor element, such as the front, bottom, and / or top surface of the capacitor element. Additionally, the coating may also contact at least a portion of the anode lead. In another embodiment, an interfacial coating may be used that covers at least a portion of the cathode termination. In such an embodiment, the coating may also contact at least a portion of a surface of the capacitor element, such as the back, top, and / or bottom surface. Referring again to FIG. 1, for example, capacitor 30 is shown having an interfacial coating 90 present on anode termination 62. More specifically, in the embodiment shown, coating 90 contacts second part 67 and fourth part 69 of anode termination 62 such that region 51 is generally covered. Coating 90 also contacts at least a portion of anode lead 16, particularly at locations around region 51 where lead 16 is connected to anode termination 62. Of course, it should be understood that the coating may be provided in other configurations and may be disposed on any surface desired. For example, in one embodiment, the coating may contact only the second component 67 of the anode termination 62.

[0058] Regardless of where it is located, the resinous material used in the interfacial coating can be selectively controlled to impart some desired property to the resulting capacitor. For example, in one embodiment, the interfacial coating includes a hydrophobic resinous material, such as a low surface energy polymer (e.g., fluoropolymer, silicone), organometallic compound, etc. Fluoropolymers can include, for example, hydrocarbon backbone polymers (e.g., polyolefins) in which some or all of the hydrogen atoms are substituted with fluorine groups such as fluoroalkyl groups (e.g., trifluoromethyl, trifluoroethyl, etc.). Backbone polymers can also be formed from ethylenically unsaturated monomers (e.g., olefins, olefinic acrylates, olefinic methacrylates, etc.). Suitable monomers can have, for example, carbon chains from 3 to 20 atoms in length, in some embodiments from 6 to 12 carbon atoms in length, and in some embodiments from 8 to 10 carbon atoms in length. Particularly suitable fluoroalkyl-substituted monomers for use in the present invention are fluoroalkyl (meth)acrylates such as perfluorohexyl (meth)acrylate, perfluoroheptyl (meth)acrylate, perfluorooctyl (meth)acrylate, perfluorononyl perfluorodecyl (meth)acrylate, perfluoroundecyl (meth)acrylate, or perfluorododecyl (meth)acrylate, as well as mixtures thereof. As used herein, the term "(meth)acrylic" includes both acrylate and methacrylate monomers.

[0059] Another suitable low surface energy polymer that can be used is a silicone polymer. Such a polymer typically has the following general formula (IV):

[0060] [ka]

[0061] (In the formula, y is an integer greater than 1; R8 , R 9 , R 10 , R 11 , R 12 , R 13 , R 14 , and R 15 are independently monovalent groups typically containing from 1 to about 20 carbon atoms, such as alkyl groups (e.g., methyl, ethyl, propyl, pentyl, octyl, undecyl, octadecyl, etc.); alkoxy groups (e.g., methoxy, ethoxy, propoxy, etc.); carboxyalkyl groups (e.g., acetyl); cycloalkyl groups (e.g., cyclohexyl); alkenyl groups (e.g., vinyl, allyl, butenyl, hexenyl, etc.); aryl groups (e.g., phenyl, tolyl, xylyl, benzyl, 2-phenylethyl, etc.); and halogenated hydrocarbon groups (e.g., 3,3,3-trifluoropropyl, 3-chloropropyl, dichlorophenyl, etc.). The polyorganosiloxanes are derived from polyorganosiloxanes such as those having the formula: ##STR1## Examples of such polyorganosiloxanes include, for example, polydimethylsiloxane (PDMS), polymethylhydrogensiloxane, dimethyldiphenylpolysiloxane, dimethyl / methylphenylpolysiloxane, polymethylphenylsiloxane, methylphenyl / dimethylsiloxane, vinyldimethyl terminated polydimethylsiloxane, vinylmethyl / dimethylpolysiloxane, vinyldimethyl terminated vinylmethyl / dimethylpolysiloxane, divinylmethyl terminated polydimethylsiloxane, vinylphenylmethyl terminated polydimethylsiloxane, dimethylhydro terminated polydimethylsiloxane, methylhydro / dimethylpolysiloxane, methylhydro terminated methyloctylpolysiloxane, methylhydro / phenylmethylpolysiloxane, fluoro-modified polysiloxanes, and the like. The polyorganosiloxanes can be crosslinked to form hydrophobic materials using any of a variety of known techniques, such as by catalytic cure (e.g., platinum catalysis), room temperature vulcanization, moisture cure, and the like. Crosslinkers such as alkoxysilanes having the formula: Si-OR, where R is H, alkyl (eg, methyl), alkenyl, carboxyalkyl (eg, acetyl), can be used.

[0062] Of course, other hydrophobic materials may also be used in the interface coating. For example, in one embodiment, the hydrophobic material may have the general formula:

[0063] [ka]

[0064] (In the formula, M is an organometallic atom such as silicon, titanium, etc.; R 16 , R 17 , and R 18 are independently alkyl (e.g., methyl, ethyl, propyl, etc.) or hydroxyalkyl (e.g., hydroxymethyl, hydroxyethyl, hydroxypropyl, etc.), and R 16 , R 17 , and R 18 at least one of is hydroxyalkyl; n is an integer from 0 to 8, in some embodiments from 1 to 6, and in some embodiments from 2 to 4 (e.g., 3); and X is an organic or inorganic functional group such as glycidyl, glycidyloxy, mercapto, amino, vinyl, etc. Examples of organometallic compounds include those having the formula:

[0065] In some embodiments, R 16 , R 17 , and R 18 is hydroxyalkyl (e.g., OCH 3 However, in other embodiments, R 16 is alkyl (e.g. CH 3 ), and R 17 and R 18 is hydroxyalkyl (e.g., OCH 3 ) may be.

[0066] In some embodiments, M can be silicon and the organometallic compound is an organosilane compound, such as an alkoxysilane. Suitable alkoxysilanes include, for example, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropylmethyldiethoxysilane, glycidoxymethyltrimethoxysilane, glycidoxymethyltriethoxysilane, glycidoxymethyltripropoxysilane, glycidoxymethyltributoxysilane, β-glycidoxyethyltrimethoxysilane, β-glycidoxyethyltriethoxysilane, β-glycidoxyethyltripropoxysilane, β-glycidoxyethyltributoxysilane, β-glycidoxyethyltrimethoxysilane, α-glycidoxyethyl glycidoxypropyltriethoxysilane, α-glycidoxyethyltripropoxysilane, α-glycidoxyethyltributoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-glycidoxypropyltripropoxysilane, γ-glycidoxypropyltributoxysilane, β-glycidoxypropyltrimethoxysilane, β-glycidoxypropyltriethoxysilane, β-glycidoxypropyltripropoxy Silane, α-glycidoxypropyl tributoxysilane, α-glycidoxypropyl trimethoxysilane, α-glycidoxypropyl triethoxysilane, α-glycidoxypropyl tripropoxysilane, α-glycidoxypropyl tributoxysilane, γ-glycidoxybutyl trimethoxysilane, δ-glycidoxybutyl triethoxysilane, δ-glycidoxybutyl tripropoxysilane, δ-glycidoxybutyl tributoxysilane, δ-glycidoxybutyl glycidoxybutyltrimethoxysilane, γ-glycidoxybutyltriethoxysilane, γ-glycidoxybutyltripropoxysilane, γ-propoxybutyltributoxysilane, δ-glycidoxybutyltrimethoxysilane, δ-glycidoxybutyltriethoxysilane, δ-glycidoxybutyltrippropoxysilane, α-glycidoxybutyltrimethoxysilane, α-glycidoxybutyltriethoxysilane, α-glycidoxybutyltrippropoxysilane, α-glycidoxybutyltributoxysilane, (3,4-epoxycyclohexyl)-methyltrimethoxysilane, (3,4-epoxycyclohexyl)methyltriethoxysilane, (3,4-epoxycyclohexyl)methyltrippropoxysilane, (3,4-epoxycyclohexyl)methyltributoxysilane, (3,4-epoxycyclohexyl)methyl (sil)ethyltrimethoxysilane, (3,4-epoxycyclohexyl)ethyltriethoxysilane, (3,4-epoxycyclohexyl)ethyltripropoxysilane, (3,4-epoxycyclohexyl)ethyltributoxysilane, (3,4-epoxycyclohexyl)propyltrimethoxysilane, (3,4-epoxycyclohexyl)propyltriethoxysilane, (3,4-epoxycyclohexyl)propyltripropoxysilane, (3,4-epoxycyclohexyl)propyltributoxysilane, (3,4-epoxycyclohexyl)butyltrimethoxysilane, (3,4-epoxycyclohexyl)butyltriethoxysilane, (3,4-epoxycyclohexyl)butyltripropoxysilane, (3,4-epoxycyclohexyl)butyltributoxysilane, and the like can be mentioned.

[0067] To help aid in its application, the interfacial coating may first be prepared in the form of a coating formulation that includes the hydrophobic resinous material in combination with an organic solvent that is typically liquid at room temperature. When used, such solvents typically comprise from about 90% to about 99.9% by weight of the formulation, in some embodiments from about 92% to about 99.8% by weight, and in some embodiments from about 95% to about 99.5% by weight, while the hydrophobic resinous material may comprise from about 0.1% to about 10% by weight, in some embodiments from about 0.2% to about 8% by weight, and in some embodiments from about 0.5% to about 5% by weight of the solution. The solvent or solvents used will depend in part on the nature of the resinous material, but generally include organic alcohols, hydrocarbon solvents, fluorinated hydrocarbon solvents, and the like. For example, solvents particularly suitable for use with fluoropolymers include fluorinated hydrocarbon solvents, such as hydrofluoroethers, fluorinated ketones, fluorinated olefins, and the like. For example, in one particular embodiment, the coating formulation may include a fluoropolymer having the following general structure (VI): (R 1 -O) x -R 2 (VI) (In the formula, x is 1 or 2; R 1 and R 2 one of which is a perfluoroaliphatic or perfluorocyclic group, and the other is an aliphatic or cyclic hydrocarbon group. For example, hydrofluoroethers having R 1 and / or R 2 can include substituted and unsubstituted alkyl, aryl, and alkylaryl groups, and derivatives thereof. Representative examples of suitable hydrofluoroethers include the following compounds: 5 F 11 O.C. 2 H 5 , C 3 F 7 OCH 3 , C 4 F 9 OCH 3 , C 4 F 9O.C. 2 H 5 , C 3 F 7 OCF(CF 3 )CF 2 OCH 3 , C 4 F 9 O.C. 2 F 4 O.C. 2 F 4 O.C. 2 H 5 , C 4 F 9 O(CF 2 ) 3 OCH 3 , C 3 F 7 CF(OC 2 H 5 )CF(CF 3 ) 2 , C 2 F 5 CF(OCH 3 )CF(CF 3 ) 2 , C 4 F 9 O.C. 2 H 4 O.C. 4 F 9 Ethyl nonafluoroisobutyl ether and ethyl nonafluorobutyl ether (both of which have the structure: C 4 F 9 O.C. 2 H 5 is particularly preferred.

[0068] III. Casing material: As shown, the capacitor element and anode lead are typically encapsulated in a casing material such that at least a portion of the anode and cathode terminations are exposed for mounting onto a circuit board. 1, for example, capacitor element 33 and anode lead 16 may be encapsulated within casing material 28 such that a portion of anode termination 62 and a portion of cathode termination 72 are maintained exposed. As noted above, the resinous matrix used to form the casing material has a relatively low coefficient of thermal expansion, which helps reduce the likelihood that it will delaminate from the capacitor element when exposed to high temperatures. The resinous matrix is ​​also generally substantially hydrophobic.

[0069] For example, in some embodiments, the resinous matrix may include a polycyanate containing at least two cyanate ester groups. For example, upon curing, the polycyanate may form a polycyanurate having a triazine ring. Due to the high degree of symmetry in the triazine ring where the dipoles associated with the carbon-nitrogen and carbon-oxygen bonds are balanced, the resulting polycyanurate may exhibit a relatively low thermal expansion. Suitable polycyanates include, for example, bisphenol A dicyanate; 4,4'-dihydroxydiphenyl, 4,4'-dihydroxydiphenyl oxide, resorcinyl, hydroquinone, 4,4'-thiodiphenol, 4,4'-sulfonyldiphenyl, 3,3',5,5'-tetrabromobisphenol A, 2,2',6,6'-tetrabromobisphenol A, 2,2'-dihydroxydiphenyl, 3,3'-dihydroxybisphenol A, 4,4'-dihydroxydiphenyl carbonate, and the like. dicyanates of dicyclopentadiene diphenol, 4,4'-dihydroxybenzophenone, 4,4'-dihydroxydiphenylmethane, tricyclopentadiene diphenol, and the like; tricyanate of tris(hydroxyphenyl)methane, tetracyanate of 2,2',4,4'-tetrahydroxydiphenylmethane, polycyanate of phenol formaldehyde condensation product (novolak); polycyanate of condensation product of dicyclopentadiene and phenol; and the like. If desired, the polycyanate may also be a C cyclohexene, including cyclopentadiene, norbornane, bornane, norbornadiene, tetrahydroindene, methyltetrahydroindene, dicyclopentadiene, bicyclo-(2,2,1)-hepta-2,5-diene, 5-methylene-2-norbornene, 5-ethylidene-2-norbornene, 5-propenyl-2-norbornene, 5-(4-cyclopentenyl)-2-norbornene, 5-cyclohexylidene-2-norbornene, 5-vinyl-2-norbornene, and the like. 7 ~C 20The polycyclic aliphatic group may include one or more polycyclic aliphatic groups that include two or more cyclic rings, such as polycyclic aliphatic groups. For example, in one particular embodiment, the polycyanate may be a dicyclopentadiene bisphenol cyanate ester. Without intending to be limited by theory, it is believed that such polycyclic groups can act as non-polar bridging groups for the polycyanate, which helps improve resistance to thermal expansion.

[0070] The resinous matrix may also include an epoxy resin, either alone or in combination with a polycyanate. When used in combination, the epoxy resin may react with the polycyanate upon curing to form copolymers and / or crosslinks with the polycyanate resin. Examples of suitable epoxy resins include, for example, bisphenol A type epoxy resins, bisphenol F type epoxy resins, phenol novolac type epoxy resins, orthocresol novolac type epoxy resins, brominated epoxy resins and biphenyl type epoxy resins, cycloaliphatic epoxy resins, glycidyl ester type epoxy resins, glycidyl amine type epoxy resins, cresol novolac type epoxy resins, naphthalene type epoxy resins, phenol aralkyl type epoxy resins, cyclopentadiene type epoxy resins, heterocyclic epoxy resins, and the like. However, it is particularly desirable to use epoxy phenol novolac (EPN) resins, which are glycidyl ethers of phenol novolac resins, to help provide the desired degree of resistance to thermal expansion. These resins can be prepared, for example, by reacting phenols with excess formaldehyde in the presence of an acid catalyst to produce a phenolic novolac resin. with epichlorohydrin in the presence of sodium hydroxide to produce novolac epoxy resins. Specific examples of novolac-type epoxy resins include phenol-novolac epoxy resins, cresol-novolac epoxy resins, naphthol-novolac epoxy resins, naphthol-phenol co-condensed novolac epoxy resins, naphthol-cresol co-condensed novolac epoxy resins, brominated phenol-novolac epoxy resins, and the like. Regardless of the type of resin selected, the resulting phenol novolac epoxy resins will usually have more than two oxirane groups and can be used to produce cured coating compositions with high crosslink density, which may be particularly suitable for increasing resistance to thermal expansion. One such phenol novolac epoxy resin is poly[(phenyl glycidyl ether)-co-formaldehyde]. Other suitable resins are available from Huntsman under the ARALDITE trade name (e.g., GY289, EPN1183, EP1179, EPN1139, and EPN 1138).

[0071] The polycyanate and / or epoxy resins can be crosslinked with a co-reactant (hardener) to further improve the mechanical properties of the composition and also increase its resistance to thermal expansion as discussed above. Examples of such co-reactants include, for example, polyamides, amidoamines (e.g., aromatic amidoamines such as aminobenzamide, aminobenzanilide, and aminobenzenesulfonamide), aromatic diamines (e.g., diaminodiphenylmethane, diaminodiphenylsulfone, and the like), aminobenzoates (e.g., trimethylene glycol di-p-aminobenzoate, and neopentyl glycol di-p-aminobenzoate), aliphatic amines (e.g., triethylenetetramine, isophoronediamine), alicyclic amines (e.g., isophoronediamine), imidazole derivatives, guanidines (e.g., tetramethylguanidine), carboxylic anhydrides (e.g., methylhexahydrophthalic anhydride), carboxylic hydrazides (e.g., adipic hydrazide), phenol-novolac resins (e.g., phenol novolac, cresol novolac, and the like), carboxylic amides, and the like, as well as combinations thereof. Phenol-novolac resins may be particularly suitable for use in the present invention.

[0072] The casing material may also include inorganic oxide fillers. Such fillers are typically maintained at high levels, such as from about 75% to about 99.5%, in some embodiments from about 76% to about 99%, and in some embodiments from about 77% to about 90% by weight of the casing material, while the resinous matrix typically comprises from about 0.5% to about 25%, in some embodiments from about 1% to about 24%, and in some embodiments from about 10% to about 23% by weight of the casing material. The nature of the inorganic oxide fillers may include silica, alumina, zirconia, magnesium oxide, iron oxides (e.g., iron hydroxide oxide yellow), titanate, and the like. The inorganic oxide filler may vary from inorganic oxides (e.g., titanium dioxide), zinc oxides (e.g., boron zinc hydroxide oxide), copper oxides, zeolites, silicates, clays (e.g., smectite clays), and the like, and composites (e.g., alumina-coated silica particles), and mixtures thereof. Regardless of the particular filler used, however, a significant portion, if not all, of the inorganic oxide filler will usually be in the form of silica glass, which is believed to further enhance the moisture resistance of the casing material due to its high purity and relatively simple chemical form. The silica glass may, for example, comprise about 30% or more by weight, in some embodiments from about 35% to about 90% by weight, in some embodiments from about 40% to about 80% by weight, of the total weight of the fillers used in the composition, as well as about 20% to about 70% by weight, in some embodiments from about 25% to about 65% by weight, and in some embodiments from about 30% to about 60% by weight of the total composition. Of course, other forms of silica, such as quartz, fumed silica, cristobalite, and the like, can also be used in combination with the silica glass.

[0073] It should be understood that, apart from the components listed above, still other additives may also be used in the casing material, such as photoinitiators, viscosity modifiers, suspending aids, pigments, stress reducers, coupling agents (e.g., silane coupling agents), stabilizers, etc. If used, such additives will typically comprise from about 0.1 to about 20% by weight of the total composition.

[0074] The particular method of applying the casing material to the capacitor element can vary as desired. In one particular aspect, the capacitor element is placed in a mold and the casing material is applied to the capacitor element such that it occupies the space defined by the mold and exposes at least a portion of the anode and cathode terminations. The casing material can be initially provided in the form of a single or multiple compositions. For example, a first composition can include the resinous matrix and filler, and a second composition can include the co-reactant. Regardless, once applied, the casing material can be heated or allowed to stand at ambient temperature to allow the resinous matrix to crosslink with the co-reactant, thereby curing and solidifying the casing material into the desired shape of the case. For example, the casing material can be heated to a temperature of from about 15° C. to about 150° C., in some embodiments from about 20° C. to about 120° C., and in some embodiments from about 25° C. to about 100° C.

[0075] Although by no means required, a moisture barrier layer may also be used which covers all or a portion of the casing material. Moisture barrier layers are generally formed from hydrophobic materials such as those described above, e.g., silicones, fluoropolymers, organometallic compounds, and the like. EXAMPLES

[0076] The invention may be better understood with reference to the following examples. Test procedure: capacitance: Capacitance was measured using a Keithley 3330 precision LCZ meter with Kelvin leads. The capacitance can be measured using a DC bias of 2.2 volts and a sine wave signal of 0.5 volts peak-to-peak. The operating frequency can be 120 Hz and the temperature can be 23°C ± 2°C. In some cases, the "wet-to-dry" capacitance can be determined. "Dry capacitance" refers to the capacitance of the part before application of the solid electrolyte, graphite, and silver layers, while "wet capacitance" refers to the capacitance of the part after dielectric formation, and is measured after 30 seconds of electrolyte immersion, in 14% nitric acid, referenced to a 1 mF tantalum cathode, using a DC bias of 10 volts and a sine wave signal of 0.5 volts peak-to-peak.

[0077] Equivalent series resistance (ESR): The equivalent series resistance was measured using a Keithley 3330 precision LCZ meter with Kelvin leads at 2 The measurements may be taken with a DC bias of 0.2 volts and a sine wave signal of 0.5 volts peak-to-peak. The operating frequency may be 100kHz and the temperature may be 23°C ±2°C.

[0078] Loss factor: Loss factor was measured using a Keithley 3330 precision LCZ meter with Kelvin leads at 2.2. The measurements may be taken with a DC bias of 1.5 V and a sine wave signal of 0.5 V peak-to-peak. The operating frequency may be 120 kHz and the temperature may be 23 °C ± 2 °C.

[0079] Leakage Current: The leakage current may be measured using a leakage test meter at a temperature of 23°C ± 2°C and rated voltage after a minimum of 60 seconds.

[0080] High temperature storage test: The high temperature storage test is based on IEC-60068-2-2:2007 (Condition Bb, temperature 125°C). All ESR measurements are performed at a temperature of 23°C + 2°C after 1-2 hours recovery from the test conditions. The samples are not mounted on a board. For a range of samples (e.g. 25 samples), the ratio of the actual ESR(average) of all tested units to the initial ESR(average) is determined.

[0081] Example 1: Anode samples were prepared using 50,000 μFV / g tantalum powder. Each anode sample was embedded with a tantalum wire, sintered at 1350 °C, and pressed to a mass of 5.8 g / cm. 3 The resulting pellet had dimensions of 1.7×2.4×1.0 mm. The pellet was anodized to 23.5 volts in a water / phosphoric acid electrolyte having a conductivity of 8.6 mS / cm at a temperature of 85° C. to form a dielectric layer. The pellet was anodized again to 80 volts for 25 seconds in a water / boric acid / disodium tetraborate electrolyte having a conductivity of 2.0 mS / cm at a temperature of 30° C. to form a thicker oxide layer deposited on the outside.

[0082] A conductive polymer coating was then formed by immersing the anode in a butanol solution of iron(III) toluenesulfonate (Clevios® C, HC Starck) followed by 3,4-ethylenedioxythiophene (Clevios® M, HC Starck) and polymerizing. After 45 minutes of polymerization, a thin layer of poly(3,4-ethylenedioxythiophene) was formed on the surface of the dielectric. The anode was washed in methanol to remove reaction by-products, anodized in liquid electrolyte, and washed again in methanol. This process was repeated six times. The part was then immersed in a dispersed poly(3,4-ethylenedioxythiophene) (Clevios® K, Heraeus) with a solids content of 2.0% and a viscosity of 20 mPa·s. Once coated, the part was dried at 125° C. for 20 minutes. This process was repeated three times. The parts were then immersed in a dispersed poly(3,4-ethylenedioxythiophene) (Clevios® K, Heraeus) with a solids content of 2.0% and a viscosity of 160 mPa·s. Once coated, the parts were dried at 125° C. for 20 minutes. This process was repeated 12 times. The parts were then immersed in a graphite dispersion and allowed to dry. Finally, the parts were immersed in a silver dispersion and allowed to dry. A large number of parts (2,000) of 47 μF / 10 V capacitors were thus made and encapsulated in a silica-filled resin with a temperature coefficient of 13 ppm / ° C. below the glass transition temperature and 51 ppm / ° C. above the glass transition temperature.

[0083] Example 2: Capacitors were formed as described in Example 1, except that the resulting parts were encapsulated in a resinous matrix as described herein. Twenty-five parts of the 47 μF / 10V capacitor were formed and then subjected to the high temperature storage test described above. The results are shown in Table 1 below.

[0084] [Table 1]

[0085] These and other modifications and variations of the present invention may be implemented by those skilled in the art without departing from the spirit and scope of the present invention. Moreover, it should be understood that aspects of the various aspects may be interchanged both in whole or in part. Moreover, those skilled in the art will recognize that the above description is by way of example only and is not intended to limit the invention as further described in the appended claims.

Claims

1. A solid electrolytic capacitor, A capacitor element including a sintered porous anode body, a dielectric disposed on the anode body, and a solid electrolyte disposed on the dielectric; an anode lead extending from a surface of the capacitor element; an anode termination electrically connected to the anode lead, and a cathode termination electrically connected to the solid electrolyte; and a casing material encapsulating the capacitor element and the anode lead, the casing material being formed from a curable resinous matrix having a coefficient of thermal expansion of about 42 ppm / ° C. or less at a temperature above a glass transition temperature of the resinous matrix; Including; The solid electrolytic capacitor as described above, wherein the capacitor exhibits an initial equivalent series resistance of about 200 milliohms or less, as determined at an operating frequency of 100 kHz and a temperature of 23° C., and a ratio of the equivalent series resistance of the capacitor after exposure to a temperature of 125° C. for 560 hours to the initial equivalent series resistance of the capacitor is about 2.0 or less.

2. 10. The solid electrolytic capacitor of claim 1, wherein the resinous matrix has a coefficient of thermal expansion of about 11 ppm / [deg.] C. or less at a temperature below the glass transition temperature of the resinous matrix.

3. 10. The solid electrolytic capacitor of claim 1, wherein the resinous matrix has a glass transition temperature of about 50°C to about 180°C.

4. 10. The solid electrolytic capacitor of claim 1, wherein the ratio of the equivalent series resistance of the capacitor after exposure to a temperature of 125° C. for 750 hours to the initial equivalent series resistance of the capacitor is less than or equal to about 2.

0.

5. 10. The solid electrolytic capacitor of claim 1, wherein the ratio of the equivalent series resistance of the capacitor after exposure to a temperature of 125° C. for 1,000 hours to the initial equivalent series resistance of the capacitor is less than or equal to about 2.

0.

6. 10. The solid electrolytic capacitor of claim 1, wherein the ratio of the equivalent series resistance of the capacitor after exposure to a temperature of 125° C. for 1,250 hours to the initial equivalent series resistance of the capacitor is less than or equal to about 2.

0.

7. 10. The solid electrolytic capacitor of claim 1, wherein an interfacial coating covers at least a portion of the anode termination.

8. 8. The solid electrolytic capacitor of claim 7, wherein the interfacial coating also covers at least a portion of the anode lead.

9. 8. The solid electrolytic capacitor of claim 7, wherein the interfacial coating comprises a fluoropolymer, a silicone polymer, an organometallic compound, or a combination thereof.

10. 10. The solid electrolytic capacitor of claim 1, wherein the resinous matrix comprises a polycyanate containing at least two cyanate ester groups.

11. 11. The solid electrolytic capacitor of claim 10, wherein the polycyanate comprises a polycyclic aliphatic group containing two or more cyclic rings.

12. The solid electrolytic capacitor of claim 11, wherein the polycyclic aliphatic group comprises cyclopentadiene, norbornane, bornane, norbornadiene, tetrahydroindene, methyltetrahydroindene, dicyclopentadiene, bicyclo-(2,2,1)-hepta-2,5-diene, 5-methylene-2-norbornene, 5-ethylidene-2-norbornene, 5-propenyl-2-norbornene, 5-(4-cyclopentenyl)-2-norbornene, 5-cyclohexylidene-2-norbornene, 5-vinyl-2-norbornene, or a combination thereof.

13. 13. The solid electrolytic capacitor of claim 12, wherein the polycyanate is a dicyclopentadiene bisphenol cyanate ester.

14. The solid electrolytic capacitor of claim 1 , wherein the resinous matrix comprises an epoxy resin.

15. 15. The solid electrolytic capacitor of claim 14, wherein the epoxy resin is a phenol novolac epoxy resin.

16. 16. The solid electrolytic capacitor according to claim 15, wherein the phenol novolac epoxy resin is a phenol-novolac epoxy resin, a cresol-novolac epoxy resin, a naphthol-novolac epoxy resin, a naphthol-phenol co-condensed novolac epoxy resin, a naphthol-cresol co-condensed novolac epoxy resin, a brominated phenol-novolac epoxy resin, or a combination thereof.

17. 10. The solid electrolytic capacitor of claim 1, wherein the resinous matrix further comprises an inorganic oxide filler in an amount of about 75% to about 99.5% by weight of the matrix.

18. 20. The solid electrolytic capacitor of claim 17, wherein the inorganic oxide filler comprises silica.

19. 10. The solid electrolytic capacitor of claim 1, wherein the capacitor element further comprises a cathode coating comprising a metal particle layer disposed on the solid electrolyte, the metal particle layer comprising a plurality of conductive metal particles.

20. 20. The solid electrolytic capacitor of claim 19, wherein the metal particles comprise silver.

21. 10. The solid electrolytic capacitor of claim 1, wherein the anode body comprises tantalum.

22. The solid electrolytic capacitor of claim 1 , wherein the solid electrolyte comprises a conductive polymer.

23. The conductive polymer has the following formula: 【Chemistry 1】 (In the formula, R 7 is linear or branched, C 1 ~C 18 Alkyl group, C 5 ~C 12 Cycloalkyl group, C 6 ~C 14 Aryl group, C 7 ~C 18 aralkyl groups, or combinations thereof; and q is an integer from 0 to 8.

23. The solid electrolytic capacitor of claim 22 having a repeat unit of:

24. 24. The solid electrolytic capacitor of claim 23, wherein the extrinsic conductive polymer is poly(3,4-ethylenedioxythiophene) or a derivative thereof.

25. 23. The solid electrolytic capacitor of claim 22, wherein the solid electrolyte also includes a polymeric counterion.

26. 10. The solid electrolytic capacitor of claim 1, further comprising an outer polymer coating disposed over the solid electrolyte, the outer polymer coating comprising prepolymerized conductive polymer particles and a crosslinker.